2006
DOI: 10.1103/physrevd.74.114026
|View full text |Cite
|
Sign up to set email alerts
|

Duality, analyticity, andtdependence of generalized parton distributions

Abstract: Basing upon dual analytic models, we present arguments in favor of the parametrization of generalized parton distributions (GPD) in the form ∼ (x/g 0 ) (1−x)α(t) , whereα(t) = α(t) − α(0) is the nonlinear part of the Regge trajectory and g 0 is a parameter, g 0 > 1. For linear trajectories it reduces to earlier proposals. We compare the calculated moments of these GPD with the experimental data on form factors and find that the effects from the nonlinearity of Regge trajectories are large. By Fourier-transform… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 87 publications
0
11
0
Order By: Relevance
“…This assumption, due to its simplicity, is widely used in the literature, although it contradicts the Regge-pole theory, as shown, e.g., in studies of DVCS or GPDs, as shown, e.g., in Refs. [15,16]. We believe that the distinct assumptions for the t dependence will introduce an uncertainty on the overall normalization as we are considering only t-integrated cross sections in current study.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…This assumption, due to its simplicity, is widely used in the literature, although it contradicts the Regge-pole theory, as shown, e.g., in studies of DVCS or GPDs, as shown, e.g., in Refs. [15,16]. We believe that the distinct assumptions for the t dependence will introduce an uncertainty on the overall normalization as we are considering only t-integrated cross sections in current study.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…This ansatz reproduces the basic properties of F 1 and provides a good description of the ratio of F 1 to F 2 and, consequently, of the ratio of G E to G M . A similar approach was examined in [28] with GPDs form…”
Section: Introductionmentioning
confidence: 99%
“…This result would pave the roads from the experimental data related to the amplitudes of the processes γ * p → γp (deeply virtual Compton scattering (DVCS)) and hard meson exclusive production γ * p → Mp to the studies of hadron structure in the two-dimensional transverse space. For the first time position space aspects of parton model were studied in the paper [8].A common procedure of obtaining GPD dependence is to guess the form of H q (x, ξ, t) proceeding from the model assumptions, namely use of the general constraints based on form-factors, first principles, experience gained from highenergy scattering and experimental studies of DVCS [10,11,12,13,14,15,16]. However, since impact parameter representation provides a useful framework for implementing geometrical aspects as well as transparent account of the unitarity constraints, it can be used as a complementary way for the GPD's modelling.…”
mentioning
confidence: 99%
“…A common procedure of obtaining GPD dependence is to guess the form of H q (x, ξ, t) proceeding from the model assumptions, namely use of the general constraints based on form-factors, first principles, experience gained from highenergy scattering and experimental studies of DVCS [10,11,12,13,14,15,16]. However, since impact parameter representation provides a useful framework for implementing geometrical aspects as well as transparent account of the unitarity constraints, it can be used as a complementary way for the GPD's modelling.…”
mentioning
confidence: 99%